2005
DOI: 10.1115/1.1852483
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Procedure for the Laminar Developed Flow in a Helical Square Duct

Abstract: The incompressible fully developed laminar flow in a helically duct of square cross section is studied expressing the governing equations in terms of an orthogonal coordinate system. Numerical results are obtained with the described continuity, vorticity, and pressure (CVP) numerical method using a colocation grid for all variables. Since there are not approximations, the interaction effects of curvature, torsion and axial pressure gradient on the velocity components and the friction factor are presented. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…However, helical coiled channels with rectangular cross section are often used in cooling system for gas turbine, rocket engine, or scramjet applications [11][12][13]. Some studies about laminar flow in helical rectangular ducts have been reported [14][15][16][17][18][19][20][21]. But literatures of turbulent flow and heat transfer in helical rectangular ducts for the turbulent flow are very few.…”
Section: Introductionmentioning
confidence: 99%
“…However, helical coiled channels with rectangular cross section are often used in cooling system for gas turbine, rocket engine, or scramjet applications [11][12][13]. Some studies about laminar flow in helical rectangular ducts have been reported [14][15][16][17][18][19][20][21]. But literatures of turbulent flow and heat transfer in helical rectangular ducts for the turbulent flow are very few.…”
Section: Introductionmentioning
confidence: 99%
“…All the implementations of the CVP method that have been published up to now concern the Q3D formulation and the solution procedure has been described in detail in [3,4,6]. All the implementations of the CVP method that have been published up to now concern the Q3D formulation and the solution procedure has been described in detail in [3,4,6].…”
Section: The Cvp Formulationsmentioning
confidence: 99%
“…It was pioneered by Hatzikonstantinou et al [3] and it has been applied successfully to quasi-3D (Q3D) internal hydrodynamic [4,5] and thermal [6,7] flow problems. It was pioneered by Hatzikonstantinou et al [3] and it has been applied successfully to quasi-3D (Q3D) internal hydrodynamic [4,5] and thermal [6,7] flow problems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations